Utilizamos cookies para personalizar el contenido y la publicidad y para analizar el acceso a nuestro sitio web. Además, nuestros socios para la publicidad online reciben información pseudónima sobre su uso de nuestra página web. políticas sobre cookies y Políticas de privacidad.
 

Formulario: Matemáticas - Trigonometría ◿

Trigonometría ◿

Definiciones:

  • a: Length of Opposite
  • b: Length of Adjacent
  • c: Length of Hypothenuse
  • h: Length of Hypothenuse
  • alpha: ángulo α
  • beta: ángulo β
  • gamma: ángulo γ
  • x: a/h
  • y: b/h
  • z: a/b
Layer 1abcabcLayer 1CABα

Teorema Pitágoras

In any right triangle, the area of the square whose side is the hypotenuse (c) is equal to the sum of the areas of the squares whose sides are the two legs (a, b).

\( {\color{blue} {c}}^2 = {{\color{red} {a}}^{2}} + {{\color{OliveGreen} {b}}^{2}} \)

\( {\color{blue} {c}} = \sqrt{ {{\color{red} {a}}^{2}} + {{\color{OliveGreen} {b}}^{2}} } \)
c = Length of Hypothenuse
a = Length of Opposite
b = Length of Adjacent

\( {\color{red} {a}} = \sqrt{ {{\color{blue} {c} }^{2}} - {{\color{OliveGreen} {b} }^{2}} } \)
a = Length of Opposite
c = Length of Hypothenuse
b = Length of Adjacent

\( {\color{OliveGreen} {b}} = \sqrt{ {{\color{blue} {c} }^{2}} - {{\color{red} {a} }^{2}} } \)
b = Length of Adjacent
c = Length of Hypothenuse
a = Length of Opposite

\( {\color{blue} {c}} = \sqrt{ {{\color{red} {a}}^{2}} + {{\color{OliveGreen} {b}}^{2}} } \)
c = Length of Hypothenuse
a = Length of Opposite
b = Length of Adjacent

\( {\color{red} {a}} = \sqrt{ {{\color{blue} {c} }^{2}} - {{\color{OliveGreen} {b} }^{2}} } \)
a = Length of Opposite
c = Length of Hypothenuse
b = Length of Adjacent

\( {\color{OliveGreen} {b}} = \sqrt{ {{\color{blue} {c} }^{2}} - {{\color{red} {a} }^{2}} } \)
b = Length of Adjacent
c = Length of Hypothenuse
a = Length of Opposite


acLayer 1CABα

Seno

The sine function is a basic triogemetric function. In a right triangle, sine gives the ratio of the length of the side opposite to an angle to the length of the hypotenuse.

\( \frac{\color{red} {a}}{\color{blue} {c}} = sin\left( {{\color{red} {\alpha} }} \right) \)
x = a/h
alpha = ángulo α

\( {{\color{red} {\alpha} }} = sin^{-1}( \frac{\color{red} {a}}{\color{blue} {c}} ) \)
alpha = ángulo α
a = Length of Opposite
c = Length of Hypothenuse

\( {\color{red} {a}} = sin\left( {{\color{red} {\alpha} }} \right) \times {{\color{blue} {c} }} \)
a = Length of Opposite
alpha = ángulo α
c = Length of Hypothenuse

\( {\color{blue} {c}} = \frac{{\color{red} {a} }}{ sin\left( {{\color{red} {\alpha} }} \right) } \)
h = Length of Hypothenuse
a = Length of Opposite
alpha = ángulo α


bcLayer 1CABα

Kosinus

The cosine function is a basic triogemetric function. In a right triangle, cosine gives the ratio of the length of the side adjacent to an angle to the length of the hypotenuse.

\( \frac{\color{OliveGreen} {b}}{\color{blue} {c}} = cos\left( {{\color{red} {\alpha} }} \right) \)
y = b/h
alpha = ángulo α

\( {{\color{red} {\alpha} }} = cos^{-1}( \frac{\color{OliveGreen} {b}}{\color{blue} {c}} ) \)
alpha = ángulo α
b = Length of Adjacent
h = Length of Hypothenuse

\( {\color{OliveGreen} {b}} = cos\left( {{\color{red} {\alpha} }} \right) \times {{\color{blue} {c} }} \)
b = Length of Adjacent
alpha = ángulo α
h = Length of Hypothenuse

\( {\color{blue} {c}} = \frac{{\color{OliveGreen} {b} }}{ cos\left( {{\color{red} {\alpha} }} \right) } \)
h = Length of Hypothenuse
b = Length of Adjacent
alpha = ángulo α


abLayer 1CABα

Tangente

The tangent function is a basic triogemetric function. In a right triangle, tangent function gives the ratio of the length of the side opposite to an angle to the length of the adjacent.

\( \frac{\color{red} {a}}{\color{OliveGreen} {b}} = tan\left( {{\color{red} {\alpha} }} \right) \)
z = a/b
alpha = ángulo α

\( {{\color{red} {\alpha} }} = tan^{-1}( \frac{\color{red} {a}}{\color{OliveGreen} {b}} ) \)
alpha = ángulo α
a = Length of Opposite
b = Length of Adjacent

\( {\color{red} {a}} = tan\left( {{\color{red} {\alpha} }} \right) \times {{\color{OliveGreen} {b} }} \)
a = Length of Opposite
alpha = ángulo α
b = Length of Adjacent

\( {\color{OliveGreen} {b}} = \frac{{\color{red} {a} }}{ tan\left( {{\color{red} {\alpha} }} \right) } \)
b = Length of Adjacent
a = Length of Opposite
alpha = ángulo α


abcLayer 1CABαβγ

Transformaciones trigonométricas

\( {\color{red} {\alpha}} + {\color{OliveGreen} {\beta}} + {\color{blue} {\gamma}} = 180 \)
alpha = ángulo α
beta = ángulo β
gamma = ángulo γ

\( cos(alpha)^2+sin(alpha)^2=1 \)
alpha = ángulo α
alpha = ángulo α

\( tan(alpha)=sin(alpha)/cos(alpha) \)
alpha = ángulo α
alpha = ángulo α
alpha = ángulo α

\( cot(alpha)=1/tan(alpha) \)
alpha = ángulo α
alpha = ángulo α

\( sin(alpha)=cos(90-alpha) \)
alpha = ángulo α
alpha = ángulo α

\( cos(alpha)=sin(90-alpha) \)
alpha = ángulo α
alpha = ángulo α

\( tan(alpha)=cot(90-alpha) \)
alpha = ángulo α
alpha = ángulo α

\( sin(2*alpha)=2*sin(alpha)*cos(alpha) \)
alpha = ángulo α
alpha = ángulo α
alpha = ángulo α

\( tan(2*alpha)=2*tan(alpha)/(1-tan(alpha)^2) \)
alpha = ángulo α
alpha = ángulo α
alpha = ángulo α

\( sin(3*alpha)=3*sin(alpha)-4*sin(alpha)^3 \)
alpha = ángulo α
alpha = ángulo α
alpha = ángulo α

\( cos(alpha)^2=(1/2)+(1/2)*cos(2*alpha) \)
alpha = ángulo α
alpha = ángulo α